AL-IHSAN AL-QUR'AN PERSPECTIVE (A Study of Thematic Interpretation) - Umar, Umar; Mardan, Mardan; Salenda, Kasjim; Farhani, Aan (Jurnal Diskursus Islam, 2021)
This study aims to provide a comprehensive understanding of al-Ihsan in the view of the Koran. The less harmonious relationship in society encourages researchers to conduct research on the concept of al-Ihsan from the perspective of the Koran. The main problem of this research is how is al-Ihsan the perspective of the Qur'an? The main problems, namely 1) What is the nature of al-Ihsan from the perspective of the Koran?; 2) What is the form of al-Ihsan in the study of the Koran?; and what is the urgency of al-Ihsan in the view of the Qur'an? This research is library research or library research that is descriptive qualitative. The sources of data used are verses of the Qur'an, books of interpretation and hadith as well as other scientific books. This research uses a science of interpretation approach with thematic interpretation method (maudu'i). The data obtained were collected and sorted accordingly. The technique of analyzing and presenting data is done by content analysis. From the description and analysis carried out in the research, it is concluded that al-Ihsan from the perspective of the Koran is the best form of human action performed perfectly. Al-Ihsan is a plus (more) value of the best deed done according to its level. The best deeds are carried out both towards God, fellow human beings, and the natural environment. The actualization of ihsan is carried out with knowledge, solemnity, and sincerity and is manifested in the form of his personality integrity. All actions taken will be intended as a form of worship to Allah swt. For humans and other creatures created by Allah, it will provide more benefits and favors than doing justice. All these best deeds will continue to be improved for the sake of self-perfection.